Carbon and Silane‐based Coatings for Improved Bonding in Hybrid Metal‐Composite Applications. Issue 7 (30th May 2022) - Zoesmar, Nira; Birkle, Lena; Fuchs, Daryl; Warnck, Moritz; Wendel, Michael; Kuhn, Marcus; Taha, Iman
Abstract: Interfacial bonding in multi‐material structures is crucial for component performance. The influence of organosilane and Diamond‐Like Carbon coatings were investigated for improved bond strength of additively manufactured AlSi10Mg, CuCr1Zr and Ti6Al4V with carbon fiber reinforced polymer composite. Treated surfaces were evaluated by surface energy, contact angle, film adhesion and thickness measurements, SEM‐EDX analysis and double‐lap‐shear tests. Coating improved the bond strength by around 20 % in case of AlSi10Mg and CuCr1Zr, whereas treatment did not show any significant effect for Ti6Al4V. Abstract : Hybrid structures have great potential for lightweight applications, provided there is a good interfacial bond between the counterparts. Carbon fiber reinforced laminates were successfully bonded to silane and DLC coated alloys manufactured by the Powder Bed Fusion of Metals using a Laser Beam.